2011
DOI: 10.1007/s10823-011-9145-y
|View full text |Cite
|
Sign up to set email alerts
|

Living Arrangement Concordance and its Association with Self-Rated Health Among Institutionalized and Community-Residing Older Adults in China

Abstract: Although many studies look at the relationship between living arrangement and health among older adults, very little research takes seniors' preferred living arrangements into account. This paper uses data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) to examine what factors are associated with concordance between actual and preferred living arrangements for both institutionalized and community-residing Chinese seniors, and to investigate associations between living arrangement concordance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 75 publications
4
39
0
3
Order By: Relevance
“…Therefore, future research should collect longitudinal data and examine the dynamic nature of the living arrangements of adult children and their parents. Previous research also finds a substantial discrepancy between older Chinese adults' preferred living arrangements and their actual living arrangements, a discrepancy with negative consequences for their health and well-being (Sereny, 2011;Sereny & Gu, 2011). Future research that assesses the living arrangement preferences of both adult children and their parents may provide additional insights on coresidence.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, future research should collect longitudinal data and examine the dynamic nature of the living arrangements of adult children and their parents. Previous research also finds a substantial discrepancy between older Chinese adults' preferred living arrangements and their actual living arrangements, a discrepancy with negative consequences for their health and well-being (Sereny, 2011;Sereny & Gu, 2011). Future research that assesses the living arrangement preferences of both adult children and their parents may provide additional insights on coresidence.…”
Section: Discussionmentioning
confidence: 94%
“…Elderly Chinese parents take pride in receiving support from children (Li et al, 2009). Over half of elderly Chinese prefer intergenerational coresidence (Sereny and Gu, 2011). Given inadequate social welfare system (LaFave, 2016), 49% of Chinese over age 65 rely on their family (mostly their children) as the primary source of income (based on the author's calculation of the 2010 China Census).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it was found adult children tend to provide care and support to their elderly parents and co-reside with them as necessary (Pezzin, Pollak & Schone 2007; Wald 2008); co-residence with older parents balances a variety of both children’s and parents’ needs (Sereny & Gu 2011). In China, adult children not living with their elderly parents still provide some kinds of support and care to fulfill their filial duties (Korinek, Zimmer & Gu 2011; Sereny 2011).…”
Section: Previous Studies and The Present Research Questionmentioning
confidence: 99%